Optimasi krim tabir surya menggunakan kombinasi ekstrak kulit nanas (Ananas comosus L.) dan ekstrak kulit pepaya (Carica papaya L.) - Harmonyzha, Giga K.; Syamsurizal, Syamsurizal; Maharini, Indri (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Excessive sun exposure can cause detrimental effects on the skin. Pineapple fruit peels (Ananas comosus L.) and papaya (Carica papaya L.) contain flavonoid compounds that can serve as sunscreen. This study aims to optimize the concentration of pineapple peel extract and papaya fruit peel in sunscreen cream formulations to provide sun protection capabilities in the maximum category. Pineapple and papaya peel extraction uses the maceration method with 70% ethanol solvent. The concentration of the extract was determined utilizing the Simplex Lattice Design method incorporated in the Design Expert 10 software. Responses used for formula optimization include pH, dispersibility and SPF values of cream preparations. The composition of the optimum formula consists of 7.90% pineapple peel extract and 9.12% papaya peel extract. Evaluation of the optimum formula shows that the resulting cream preparation has a pH of 4.58, a spread power of 9.02 cm2 and an SPF value of 11.35. Preparations of the optimal formula of sunscreen cream have protective activity against ultraviolet rays in the maximum category.